The state of open government data implementation in Malaysia government agencies - Mohamad Puad, Noor Hazwani; Suhaimi, Mohd Adam; Hussin, Husnayati; Muhamad Ibrahim, Najhan (IIUM Press, 2022)
The Malaysian Administrative Modernization and Management Planning Unit (MAMPU) aims to enhance the quality of datasets published on the portal towards the year 2022. Various activities have been conducted by MAMPU to raise the publics' awareness of OGD. This paper consists of a preliminary study where the authors focus on exploring the current state of OGD implementation in Malaysia and the issues surrounding it. The methods involved are interviews and documents research. According to this preliminary study, the current issues in OGD implementation are data sharing readiness, high impact and high value data insufficiency, laws, and regulations. These findings are taken from the perspective of the key players of OGD project in Malaysia and help to provide insights for the authors' future research.